Impact of Cottage Micro Small and Medium Enterprise Financing on Bank Performance: Evidence from Emerging Economy - Naiem, Jannatul; Lalon, Raad Mozib (International Journal of Economics and Financial Issues, 2023)
This paper aims to assess the impact of Cottage, Micro, Small and Medium Enterprises (CMSMEs) financing on bank performance estimated with NIM (net interest margin) ratio followed by ROE (return on equity) and ROA (return on assets) ratio considering ten commercial banks (both private and state-owned bank) of Bangladesh being a participant of emerging economy covering from the year 2011 to the year 2020. Adopting Pooled OLS, Fixed Effect (FE), Random Effect (RE) and Generalized Least Square (GLS) technique enables the estimation of coefficients corresponding to the explanatory variables of the models constructed with bank specific as well as macroeconomic control variables along with the CMSME financing factors affecting banks’ profitability. We also use diagnostic tests like the test of heteroskedasticity, multicollinearity, omitted variable, and autocorrelation to ensure our models are accurate. From this paper it will be cleared that the growth of CMSME financing can lead to higher profitability of commercial banks, higher employment rate in CMSME sector other than any other sector. According to the estimated findings of the models, almost all CMSMSE determinants along with a few control variables including bank size, GDP growth and inflation largely account for the variations in profitability ratio of banks.